2006
DOI: 10.1007/s11481-006-9041-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for NeuroAIDS: The Widening Scope of Metabolomics

Abstract: "Metabolomics", the measurement of metabolite concentrations and fluxes in cell systems, is an emerging science that has enormous potential and several unique characteristics. The current applications for this field are, primarily, toxicological profiling and biomarker studies. This review of metabolomics research highlights the identification of reliable biomarkers with emphasis on neuroAIDS. Such identification of candidate markers will be advantageous for tracking the progression of human immunodeficiency v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…NMR ( 1 H-NMR) advantages include the theoretical possibility to detect and structurally elucidate any molecule containing hydrogen and also being very quantitative in its nature. Disadvantages include low sensitivity, typical detection limits are in the range milli-to high micromolar (Pendyala et al 2007), and also the fact that one-dimensional spectra gets very dense with spectral information resulting in more abundant metabolites masking signal of less abundant ones. Mass spectrometry advantages include high sensitivity (milli-to nanomolar) and being easily interfaced with chromatography resulting in the capability to temporally resolve the analysis of thousands of components.…”
Section: Discussionmentioning
confidence: 99%
“…NMR ( 1 H-NMR) advantages include the theoretical possibility to detect and structurally elucidate any molecule containing hydrogen and also being very quantitative in its nature. Disadvantages include low sensitivity, typical detection limits are in the range milli-to high micromolar (Pendyala et al 2007), and also the fact that one-dimensional spectra gets very dense with spectral information resulting in more abundant metabolites masking signal of less abundant ones. Mass spectrometry advantages include high sensitivity (milli-to nanomolar) and being easily interfaced with chromatography resulting in the capability to temporally resolve the analysis of thousands of components.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Riddler et al 40 demonstrated through CD4 cell count and viral load that most patients in this study were not defined as having AIDS and were therefore relatively healthy, with CD4 cell counts of above 600 cells per mm. 3 These authors therefore concluded that the majority of metabolites (organic acids) identified as being associated with HIV-induced mitochondrial damage was not associated with disease progression. The bigger problem for commenting on disease progression and associated metabolites is that the identified metabolites have not yet been quantified.…”
Section: Impact Of Metabolites On Disease Progressionmentioning
confidence: 99%
“…3,10 Metabonomics on the other hand measures the global, dynamic changes in metabolic profiles of a biological system in response to disease, drugs, etc. 3,10 For the purpose of this review, metabonomics is used to mean detecting metabolites or profiles affected by HIV/AIDS and/or its treatment. This article first sets the stage by confirming metabolic changes as a consequence of HIV infection, virus induced immune deficiency and/or HAART with acknowledgement that the largest amount of existing knowledge about HIV/AIDS related metabolic abnormalities was collected by conventional biochemical methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Such biomarker(s) will help in early detection and classification of neurocognitive impairment. 24 Furthermore, multiple reaction monitoring (MRM) 25 can also be applied to drug discovery assays in the context of HIV-1 infection of macrophages and can be used for lead selection, lead optimization, in vivo efficacy screening, and early in vivo toxicological testing. This targeted metabolomics platform can be utilized in the future as a high-throughput screening tool for identification of new biomarker(s) in plasma and CSF of HIV-1 infected individuals.…”
Section: Introductionmentioning
confidence: 99%